Social-Environmental Analysis for the Management of Coastal Lagoons in North Africa - El Mahrad, Badr; Abalansa, Samuel; Newton, Alice; Icely, John D.; Snoussi, Maria; Kacimi, Ilias (Frontiers in Environmental Science, 2020)
This study provides an overview of eleven lagoons in North Africa, from the Atlantic to the Eastern Mediterranean. Lagoons are complex, transitional, coastal zones providing valuable ecosystem services that contribute to the welfare of the human population. The main economic sectors in the lagoons included fishing, shellfish harvesting, salt and sand extraction, as well as maritime transport. Economic sectors in the areas around the lagoons and in the watershed included agriculture, tourism, recreation, industrial and urban development. Changes were also identified in land-use from reclamation, changes in hydrology, changes in sedimentology from damming, inlet modifications and coastal engineering. The human activities in and around the lagoons exert multiple pressures on these ecosystems and result in changes in the environment, affecting salinity, dissolved oxygen and erosion; changes in the ecology, such as loss of biodiversity; and changes in the delivery of valuable ecosystem services. Loss of ecosystem services such as coastal protection and seafood affect human populations that live around the lagoons and depend on them for their livelihood. Adaptive management frameworks for social- ecological systems provide options that support decision makers with science-based knowledge to deliver sustainable development for ecosystems. The framework used to support the decision makers for environmental management of these eleven lagoons is Drivers-Activities-Pressures-State Change-Impact on Welfare-Responses as Measures [ DAPSI(W)R(M)].